Design Model for Productive Zakat Program BAZNAS Based on Regional Potential Using Participation Action Research (PAR) and Geographic Information System (GIS) - Eka Sri Wahyuni (International Journal of Zakat, 2025)
This study examines the evolution and management of zakat, a fundamental Islamic practice aimed at wealth redistribution and economic empowerment. It highlights the significance of productive zakat of Badan Amil Zakat Nasional (BAZNAS), which supports recipients (mustahīq) in engaging in sustainable business activities, thereby fostering economic independence. Utilizing Participatory Action Research (PAR) and Geographic Information Systems (GIS), the research develops a model for zakat distribution that aligns with regional potentials, particularly in Bengkulu province, Indonesia. The findings reveal a predominance of consumptive zakat, yet an increasing trend towards productive allocations, especially for micro, small, and medium enterprises (MSMEs). Challenges such as inadequate irrigation and agricultural equipment were identified, necessitating targeted interventions. The proposed zakat model emphasizes collaboration among stakeholders to enhance program effectiveness and sustainability. This research contributes to the discourse on zakat management, advocating for a shift towards productive initiatives that empower mustahīq and promote economic resilience. Future studies should assess the model's applicability across diverse Indonesian contexts to further optimize zakat distribution systems.